Gestão de riscos em compras governamentais: estudo de caso na Central de Compras do Governo de Minas Gerais - Laysse Fernanda Macedo dos Santos (2018)
Public purchases are exposed to the most diverse risks, such as, deserted or failed bids, errors in the technical specification of the object to be acquired and failures in market research. In view of this scenario, there is an imperative for the implementation of risk management practices in public procurement, in order to identify the risks and reduce the exposure to risks and their consequences. Corroborating this perspective, this study aims to understand how the risks present in the processes of acquisition of goods and services are generated and managed within the scope of the Brazilian Public Administration. An exploratory, qualitative research was carried out using the case study method. The empirical field chosen for the case study was the Procurement Central of the Government of Minas Gerais. Focal groups were used as a data collection instrument. The data collected were analyzed through content analysis The results indicate that most of the identified risks are generated from internal causes to public bodies and entities and are mainly derived from three sources: (1) human failures, (2) lack of clear and well defined organizational processes, and 3) of the inconsistencies in the technology tools. The results also demonstrate that public agencies and entities are the main holders of mitigation strategies to reduce the vulnerability found in the procurement of goods and services.